Open truman1211 opened 2 years ago
We have three known equations:
inverse projection from (2D->3D): ((u0 - cx0)/fx) * z = X0
camera translation (3D->3D): X1 = X0 + baseline
projection from (3D->2D) u1 = fx*(X1/z) + cx1
Given these equations, we can rearrange and solve for z: z = (fx*baseline) / |disp + (cx1 - cx0)| where disp=u0-u1
Usually cx1 and cx0 are the same, so this term is often omitted.
"(cx1-cx0) is the x-difference of principal points.", I just can't understand why x should plus this item